Efficacy and feasibility of ruxolitinib in chronic steroid‐refractory GVHD in a pediatric intestine transplant. (27th September 2020) - Ghobrial, Shahira; Gonzalez, Corina; Yazigi, Nada; Kaufman, Stuart; Matsumoto, Cal; Fishbein, Thomas; Hawksworth, Jason; Kroemer, Alexander; Khan, Khalid
Abstract: Acute graft‐versus‐host disease (GvHD) has been a clinical problem in solid organ transplant that includes intestine due to the donor lymphoid tissue mass which accompanies the intestinal component of the graft. We report a case that demonstrated the efficacy and feasibility of ruxolitinib a JAK 1/2 inhibitor in the treatment of chronic steroid‐refractory GVHD (SR‐GVHD). The child developed SR‐GVHD following a composite intestine transplant (small bowel, colon, liver, and pancreas). And after receiving ruxolitinib 1.25 mg (0.15 mg/kg/dose) per gastric tube (G‐tube) daily, the child appeared to have improved skin rash and sigmoidoscopy was negative. Nonetheless, we encourage close monitoring of hematologic and infectious adverse effect during dose escalation, and individualizing patient maximum effective dose with the least adverse effect possible. We stress the importance of early diagnosis and hyper‐alertness of GVHD in intestinal transplant patients.